A cross-sectional study to assess levels of Activities of daily living (ADLs) among adolescents with disabilities in district Dehradun - Krishali, Akash; Srivastava, Abhay; Vyas, Shaili; Sharma, Neha (Indian Journal of Community Health, 2024)
Background: Adolescent disability conditions encompass a variety of physical, cognitive, or sensory impairments that affect individuals between ages 10 and 19 years. These conditions can significantly impact educational, social, and emotional development during a critical phase of life. Adequate support, accessibility, and awareness are essential to ensure that adolescents with disabilities can thrive and fulfill their potential. Objective: To assess the Activities of Daily Living (ADLs) in adolescents with disabilities Methodology: A School-based cross-sectional descriptive study was done among adolescents with disabilities attending special schools in district Dehradun. Simple random sampling was used as sampling technique. The study measured Activities of Daily Living (ADLs) through Barthel Index. The data was entered in MS Excel and imported to SPSS software version 22 for analysis. Result: A total of 142 study participants were selected for the study, with a mean (standard deviation) age of 14.32 years (± 0.20). 93% of the study subjects had a disability since birth (congenital). 42.3% of study participants had a Moderate dependence level. Conclusion: In conclusion, in this study of 142 participants, the prevalence of congenital disabilities among adolescents was high, and a substantial number demonstrated a moderate level of dependence, emphasizing the importance of tailored interventions for this population.